Aspidistra yangchunensis (Asparagaceae), a new species from Guangdong, China - Dong, Shu-Peng; Huang, Yi; Ning, Zu-Lin (Phytotaxa, 2024)
Aspidistra yangchunensis, a new species of Asparagaceae from Guangdong, southern China, is described and illustrated. Aspidistra yangchunensis resembles A. subrotata, but can be distinguished by the syntepalous part of perigone almost flat, 4 alternate perigone lobes folded at base in full bloom, pure white pistil, lower surface of stigma folds inward to form a circular inner space.